2023
DOI: 10.1182/blood.2022017863
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic deletion of 1p32 defines ultra-high-risk myeloma, but monoallelic del(1p32) remains a strong prognostic factor

Abstract: Cytogenetics abnormalities (CA) are known to be the preponderant prognostic factor in multiple myeloma (MM). Our team has recently developed a prognostic score based on 6 CA, where del(1p32) appears to be the second worst abnormality after del(17p). The aim of this study was to confirm the adverse impact of 1p32 deletion on newly-diagnosed multiple myeloma (NDMM) patients. Among 2551 NDMM patients, 11% were harboring del(1p32). Their overall survival (OS) was significantly inferior compared to patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…These factors could possibly explain the statistical significance of del(1p32) in PFS and OS noted in this study. 14 In another recent report of post hoc analysis of NDMM patients treated on the Eastern Cooperative Oncology Group E1A11 study, the presence of del 1p was associated an inferior PFS and OS. 28 In this study, treatment with carfilzomib, lenalidomide, and dexamethasone, but not Bortezomib, lenalidomide, dexamethasone abrogates adverse outcomes conferred by del 1p.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These factors could possibly explain the statistical significance of del(1p32) in PFS and OS noted in this study. 14 In another recent report of post hoc analysis of NDMM patients treated on the Eastern Cooperative Oncology Group E1A11 study, the presence of del 1p was associated an inferior PFS and OS. 28 In this study, treatment with carfilzomib, lenalidomide, and dexamethasone, but not Bortezomib, lenalidomide, dexamethasone abrogates adverse outcomes conferred by del 1p.…”
Section: Discussionmentioning
confidence: 96%
“…When cases with deletions and mutations of the FAM46C gene were taken together, they were associated with impaired OS 13 . In a recent report of 2551 newly diagnosed multiple myeloma (NDMM) patients, the OS of patients with biallelic del(1p32) was particularly worse at 25 months compared to 60 months with monoallelic del(1p32) 14 . Additionally, the outcomes were inferior when del(1p32) was associated with high‐risk cytogenetic abnormalities such as (del(17p), t(4;14), or 1q gain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, these results appear to be consistent with and complement the existing literature regarding the prognostic impact of del(1p) in the modern era of MM management. In addition to several historical data sets that showed poor outcomes for patients with del(1p), [12][13][14][15][16] a retrospective analysis from the Intergroupe Francophone du Myélome 17 and a post hoc analysis of the Eastern Cooperative Oncology Group E1A11 trial 18 both found that patients with del(1p) was associated with worse outcomes among patients treated with modern induction regimens.…”
mentioning
confidence: 99%